The Effect of Npk 16 16 16 Fertilizer and Time of Application on the Growth of Red Chili Plants in Afdeling 2 Plantation, West Bilah District, Labuhanbatu Regency - Mas Wahyudi; Yusmaidar Sepriani; Badrul Ainy Dalimunthe; Dini Hariyati Adam (International Journal of Science and Environment (IJSE), 2022)
The need for curly red chili plants for nutrients can be met with appropriate fertilization according to the needs of the plant itself, fertilization aims to improve plant fertility to plant growth. The purpose of this study was to determine the effect of npk16-16-16 fertilizer and application time on red chili plant growth. The research was conducted in Afdeling 2 plantation area, West Bila Subdistrict, Labuhanbatu Regency. This research was carried out from October 2021 to February 2022. The design used in this study was a randomized block design (RAK) and used a 3x3 factorial consisting of 2 factors. The first factor was the application of NPK 16 16 16 fertilizer with 3 levels, P1: a dose of 3 g/plant, P2: a dose of 6 g/plant, P3: a dose of 9 g/plant. The second factor is the application time of NPK 16-16-16 fertilizer with 3 levels, K1: once a week, K2: once every 2 weeks, K3: once every 3 weeks. Observational data were analyzed with a 5% level of variance to determine whether there was a significant difference between treatments. Followed by Duncan's New Multiple Range Test (DMRT) level 5% if there is a significant difference in each treatment. The results showed that the treatment at a dose of 9 g/plant gave a good trend in plant height growth. while the dose of 6 g/plant gave a tendency of good yields in all yields and several observations of the growth of flowering age and leaf area.